Costs and benefits of agricultural research : the state of the arts - Schuh, G. Edward; World Bank (Washington, D.C. International Bank for Reconstruction and Development., 1979)
This paper reviews the issues to be faced in allocating funds between projects and between institutions involved in agricultural research, and between agricultural research and other activities. In doing this, the authors first identify and elaborate the goals of agricultural research, including: (i) increasing consumer welfare; (ii) increasing farm employment and incomes; (iii) increasing net income of the rural sector; (iv) allowing agriculture to contribute to rural economic development; (v) preserving the environment; and (vi) promoting overall rural development. The paper goes on to identify and review a wide range of methods and procedures that might be used for evaluating the contribution and effectiveness of agricultural research programs. These include: (i) those which might be used to evaluate research efforts that have been underway for some time; and (ii) those which are appropriate in attempting to evaluate the research that is proposed but not begun. The paper then examines some of the implications of using such tools in evaluating research.
Includes bibliographical references
lje 16/06/2017
Ref
Keywords: Agriculture--Research; Agriculture--Research--Cost effectiveness